2022
DOI: 10.1093/aje/kwac164
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Pulse Oximeter Device Inaccuracy and Estimated Clinical Impact on COVID-19 Treatment Course

Abstract: Arterial blood oxygen saturation measured by pulse oximetry (SpO2) may be differentially less accurate for people with darker skin pigmentation, which could potentially affect COVID-19 treatment course. We analyzed pulse oximeter accuracy and association with COVID-19 treatment outcomes using electronic health record (EHR) data from Sutter Health, a large, mixed-payer, integrated healthcare delivery system in northern California, United States (US). We analyzed two cohorts: (1) 43,753 concurrent arterial blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The high light absorption and scattering capacity of melanin ensures that harmful UV radiation is either scattered or absorbed in the uppermost layer of the skin and therefore protects the underlaying layers from DNA photodamage 45 . Such a behavior leads to inaccuracies in optical measurements for dark skin people 46,47 due to the high absorption characteristics of melanin as well as the fact that cosmetic procedures such as hair follicle removal or port wine stain treatment are not as effective for all phenotypes 48,49 . As hypothesized in the study by Charlton et al., radiative properties of human skin may not be affected by melanin 50 .…”
Section: Resultsmentioning
confidence: 99%
“…The high light absorption and scattering capacity of melanin ensures that harmful UV radiation is either scattered or absorbed in the uppermost layer of the skin and therefore protects the underlaying layers from DNA photodamage 45 . Such a behavior leads to inaccuracies in optical measurements for dark skin people 46,47 due to the high absorption characteristics of melanin as well as the fact that cosmetic procedures such as hair follicle removal or port wine stain treatment are not as effective for all phenotypes 48,49 . As hypothesized in the study by Charlton et al., radiative properties of human skin may not be affected by melanin 50 .…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, only one pediatric publication observed no statistical difference in accuracy by skin pigmentation (25). While limited data evaluates clinical implications of occult hypoxemia in children, all published adult studies observed associations with adverse outcomes, including receipt of less supplemental oxygen, delayed COVID-19 therapies or ICU transfer, and higher organ dysfunction as well as mortality (22,(26)(27)(28)(29)(30).…”
Section: Oximetry Bias and Racementioning
confidence: 99%
“…The documented inaccuracy of pulse oximetry among individuals with dark skin tones has been a known issue for over 20 years. Moreover, the profound treatment inequities experienced by individuals with dark skin tones stemming from the limitations of pulse oximetry were particularly evident during the COVID-19 pandemic 16,17 . The underdetection of hypoxemia with pulse oximeters in persons with dark skin tones led to differences in treatment decisions including administration of supplemental oxygen, intravenous dexamethasone, and hospital admission 17 …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the profound treatment inequities experienced by individuals with dark skin tones stemming from the limitations of pulse oximetry were particularly evident during the COVID-19 pandemic. 16,17 The underdetection of hypoxemia with pulse oximeters in persons with dark skin tones led to differences in treatment decisions including administration of supplemental oxygen, intravenous dexamethasone, and hospital admission. 17 Melanin absorbs and scatters light at specific wavelengths used in the measurement process, which necessitates its consideration in measurement algorithms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation